About Semi-parametric Methodology for Fuzzy Quantile Regression Model Estimation: A Review - Baha Alwan, Elaf; Abdulmohsin Ali, Omar (Journal of Economics and Administrative Sciences, 2024)
In this paper, previous studies about Fuzzy regression had been presented. The fuzzy regression is a generalization of the traditional regression model that formulates a fuzzy environment’s relationship to independent and dependent variables. All this can be introduced by non-parametric model, as well as a semi-parametric model. Moreover, results obtained from the previous studies and their conclusions were put forward in this context. So, we suggest a novel method of estimation via new weights instead of the old weights and introduce Paper Type: Review article. another suggestion based on artificial neural networks.